Molecular correlates of platinum response in human high‐grade serous ovarian cancer patient‐derived xenografts. Issue 3 (24th January 2014) - Topp, Monique D.; Hartley, Lynne; Cook, Michele; Heong, Valerie; Boehm, Emma; McShane, Lauren; Pyman, Jan; McNally, Orla; Ananda, Sumitra; Harrell, Marisol; Etemadmoghadam, Dariush; Galletta, Laura; et al.
Abstract : Introduction: Improvement in the ability to target underlying drivers and vulnerabilities of high‐grade serous ovarian cancer (HG‐SOC) requires the development of molecularly annotated pre‐clinical models reflective of clinical responses. Methods: We generated patient‐derived xenografts (PDXs) from consecutive, chemotherapy‐naïve, human HG‐SOC by transplanting fresh human HG‐SOC fragments into subcutaneous and intra‐ovarian bursal sites of NOD/SCID IL2Rγnull recipient mice, completed molecular annotation and assessed platinum sensitivity. Results: The success rate of xenografting was 83%. Of ten HG‐SOC PDXs, all contained mutations in TP53, two were mutated for BRCA1, three for BRCA2, and in two, BRCA1 was methylated. In vivo cisplatin response, determined as platinum sensitive (progression‐free interval ≥100 d, n  = 4), resistant (progression‐free interval <100 d, n  = 3) or refractory ( n  = 3), was largely consistent with patient outcome. Three of four platinum sensitive HG‐SOC PDXs contained DNA repair gene mutations, and the fourth was methylated for BRCA1. In contrast, all three platinum refractory PDXs overexpressed dominant oncogenes ( CCNE1, LIN28B and/or BCL2 ). Conclusions: Because PDX platinum response reflected clinical outcome, these annotated PDXs will provide a unique model system for preclinical testing of novel therapies for HG‐SOC. Highlights: High‐grade serous ovarian cancer patient‐derived xenografts from fragments (83% success). In vivo platinum response (sensitive ≥ 100 d) consistent with patient outcome. Three of four platinum‐sensitive PDX contained mutations in BRCA1 or BRCA2. All three platinum refractory PDX overexpressed dominant oncogenes. These annotated PDX will enhance preclinical testing of novel therapies.